Pelatihan Digital Marketing bagi UMKM Migran Indonesia di Malaysia Menggunakan Kerangka 5A Kotler: Sebuah Program Pengabdian kepada Masyarakat - Kholil, Muhammad; Suparno, Adizty (CV. IRA PUBLISHING, 2025)
This community service program aimed to improve the digital marketing skills of Indonesian migrant SMEs in Malaysia through training based on Kotler’s 5A framework (Aware, Appeal, Ask, Act, Advocate). Conducted in collaboration with PERMAI Pulau Pinang, the program engaged 43 participants from various business sectors. Training was delivered through interactive sessions, discussions, and practical guidance focused on social media marketing, basic SEO, content creation, and customer engagement. Program effectiveness was measured using a quantitative expectation–performance approach across 12 indicators on a 5-point Likert scale. The results showed an average expectation score of 3.47 and a performance score of 3.32, indicating a small gap (−0.15) and overall alignment with participant expectations. High consistency was found in material relevance, delivery methods, and facilitator competence. However, the largest gap (−0.26) appeared in perceived tangible benefits, suggesting the need for extended implementation time. In conclusion, the training effectively enhanced participants’ awareness and understanding of digital marketing strategies. Ongoing mentoring is recommended to support sustainable application and measurable business improvement among Indonesian migrant SMEs.